Potential Woody Species and Species Attributes for Windbreaks in Florida - Michael G. Andreu; Bijay Tamang; Donald L. Rockwood; Melissa H. Friedman (EDIS)
This article offers guidance for Florida farmers and growers in the selection of woody species for windbreaks, highlighting attributes that align with sustainable agricultural practices.